Approximations of operating characteristics of the elliptic cross-section beam position monitors - Ivashchenko, V.E.; Karnaukhov, I.M.; Trotsenko, V.I.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2004)
In the specialized storage rings it is necessary to measure a position of a beam with an absolute accuracy up to 10 µm that corresponds to a relative accuracy about 10⁻³ for the central region of a monitor. The position of a beam is usually measured with the help of electrostatic button monitors. Operating characteristics of a beam position monitor are individual for each copy, are measured on precision benches and approximated by analytical functions. In the paper the various methods of approximation of operating characteristics are considered and the variant allowing one to reduce an error of approximation in tens times in comparison with a traditional method is found.